Ottawa versus Pittsburgh knee rules in screening acute knee injury - Shrestha, Sarik Kumar; Devkota, Pramod; Majagaiyan Pokhrel, Prabhav; Thakur, Abhishek Kumar (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Acute knee injuries account for eight percent of all injuries. Ottawa and Pittsburgh knee rules (OKR and PKR) were developed to assess the need for radiographs in acute knee injury. The objective of the study is to analyse the applicability of OKR and PKR to rule out fractures in acute knee injury. Method: This prospective cross-sectional study included 120 patients presenting with acute knee injury. Patients were assessed based on Ottawa and Pittsburgh knee rules (OKR and PKR) and radiographs were evaluated for fractures. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of OKR and PKR were calculated along with possible reduction in radiographs. Association of sex and age with outcome of acute knee injury was also analysed. Result: Among the 120 patients, 74(61.67%) were males and 46(38.33%) were females. Sensitivity, specificity, PPV and NPV of OKR were 95% CI 0.94(0.83-0.99), 95% CI 0.40(0.28-0.52), 95% CI 0.53(0.42-0.63) and 95% CI 0.90(0.74-0.98) respectively with possible reduction in radiographs by 31(25.83%). Sensitivity, specificity, PPV and NPV of PKR were 95% CI 0.88(0.76-0.05), 95% CI 0.57 (0.45-0.69), 95% CI 0.59(0.47-0.71) and 95% CI 0.87(0.75-0.95 ) respectively with possible reduction in radiographs by 46(38.33%). Conclusion: OKR and PKR are highly sensitive in ruling out fractures in patients with acute knee injury and more than one-fourth of radiographs can be avoided if these rules are applied.